EFFECT OF THE ION TREATMENT ON AN RNA HAIRPIN: MOLECULAR DYNAMICS STUDY - Elisabeth Catherina Widjajakusuma; Alessandra Villa; Gerhard Stock (Universitas Gadjah Mada, 2012)
Molecular dynamics has been employed to study the effect of ion treatment on the stability of 14-nucleotide RNA hairpin of Coxsackievirus B3. Three AMBER force fields were used: AMBER94, AMBER98, and AMBER99, which showed no significant structural difference of the hairpin. Thereafter, we applied two different long-range electrostatic treatments that were reaction field and PME methods, and calculated the distribution of ions around the hairpin. Although the structural stabilities of the MD simulations using both methods were similar in 0.14 M Na+, ion environment around the hairpin was notably different. In particular, structural stabilition of the hairpin with increasing ion concentration and with ion Mg2+ cannot be accommodated by simulations using reaction field method. Furthermore, the MD simulations using PME method suggested the strong similarity in structural and dynamical properties of the hairpin with 0.14 M Na+, 0.50 M Na+, 1,03 M Na+, and 0.08 M Mg2+ concentrations. However, the simulations revealed different ion occupations of Na+ and Mg2+.